Pembangunan model profesionalisme guru Pendidikan Islam berasaskan ‘Riadhah Ruhiyyah’ / Habibah @ Artini binti Ramlie - Habibah @ Artini, Ramlie (2017)
This study is aimed to develop an Islamic Education Teachers’ Professionalism Model based on 'Riadhah Ruhiyyah'. The study adopted the Design and Development Research Approach - DDR) which was introduced by Richey and Klein (2007). Four main objectives of this research were identified; review the needs of Islamic Education teachers (GPI) professionalism, identify the characteristics of Islamic Education professional teacher, developing Islamic Education teachers’ Professionalism Model based on 'Riadhah Ruhiyyah' and assess the usability of developed model. The development of the Islamic Education Teachers’ Professionalism Model is based on the Theory of Professional Teacher according to Imam Al-Ghazali combined with the Model of Teacher Changes by Guskey (2002). The study was conducted in three phases. Phase I involved needs analysis phase using survey questionnaire that was conducted among 270 respondents to investigate the requirements of GPI professionalism. Data for this phase was analyzed using descriptive analysis via IBM SPSS Statistics 20 software. After obtained findings, the researcher conducted Phase II of this study. Phase II is a model design and development phase. This phase involves two sub phases : Phase II (A) and Phase II (B). Phase II (A) is a content analysis phase towards a book with title 'Ihya' Ulum al-Din' written by Imam Al-Ghazali (t.t) that discusses the characteristics of professional teacher. Standard Guru Malaysia and professional standards of teaching some other countries documents also analysed. Phase II (B) of this study is the phase of model development using Fuzzy Delphi Method (FDM). FDM techniques adopted for the purpose of verifying the content of developed model by panel of experts of 15 members using questionnaires. Phase III of this study is a phase of the model assessment. This phase involved 21 experienced GPI to evaluate the model using Modified Nominal Group Technique. The evaluation was based on their responses to a questionnaire. The overall findings for Phase I indicated that GPI expressed high requirements for the professionalism aspects based on ‘Riadhah Ruhiyyah’ with a mean value of the overall findings was 4.492. The results of Phase II (A) identified the main characteristics of professional teacher and the aspects of 'Riadhah Ruhiyyah' meanwhile findings from Phase II (B) resulted in the development of the model from consensual agreement among the experts that consisted of three main components with 11 elements and 129 sub elements. Findings from Phase III resulted the usability of the model among GPI with high acceptance. This study finally proposes an Islamic Education Teachers’ Professionalism Model based on 'Riadhah Ruhiyyah' to fulfill the needs and standards as a GPI. In conclusion, the researcher proposed a suggestion that the Model of Islamic Education Teachers’ Professionalism based on 'Riadhah Ruhiyyah' introduced in the curriculum of training future teachers either at the institute or university while for novices or experienced teachers, this model can be introduced in the course of in-service training organized during their service.